Applying post-neoadjuvant pathologic stage as prognostic tool in esophageal squamous cell carcinoma - Han, Weiming; Deng, Wei; Wang, Qifeng; Ni, Wenjie; Li, Chen; Zhou, Zongmei; Liang, Jun; Chen, Dongfu; Feng, Qinfu; Bi, Nan; Zhang, Tao; Wang, Xin; et al. (Frontiers in Oncology, 2022)
Background: It is still uncertain whether the newly released American Joint Committee on Cancer (AJCC) 8th post-neoadjuvant pathologic (yp) Tumor-Node-Metastasis (TNM) stage for esophageal carcinoma can perform well regarding patient stratification. The current study aimed to assess the prognostication ability of the 8th AJCC ypTNM staging system and attempted to explore how to facilitate the staging system for more effective evaluation of prognosis. Materials and methods: 486 patients treated with neoadjuvant radiotherapy/chemoradiotherapy (nRT/CRT) were enrolled. ypN stage was reclassified by recursive partitioning. Prognostic performance, monotonicity, homogeneity, and discriminatory of yp and modified yp (myp) staging systems were assessed by time-dependent receiver operating characteristic (ROC), linear trend log-rank test, likelihood ratio χ2 test, Harrell’s c statistic, and Akaike information criterion (AIC). Results: ypT, ypN stage, pathologic response were significant prognostic factors of overall survival. Survival was not discriminated well using the 8th AJCC ypN stage and ypTNM stage. Recursive partitioning reclassified mypN0-N2 as metastasis in 0, 1-2 and ≥3 regional lymph nodes. Applying ypT stage, mypN stage and pathologic response to construct myp staging system, myp stage performed better in time-dependent ROC, linear trend log-rank test, likelihood ratio χ2 test, Harrell’s c statistic, and AIC. Conclusions: The 8th AJCC ypTNM staging system performed well in differentiating prognosis to some extent. By reclassifying ypN stage and enrolling pathologic response as a staging element, the myp staging system holds significant potential for prognostic discrimination.